2012
DOI: 10.3892/or.2012.1804
|View full text |Cite
|
Sign up to set email alerts
|

L-carnitine and cancer cachexia. I. L-carnitine distribution and metabolic disorders in cancer cachexia

Abstract: Abstract. Cancer cachexia (CC), a progressive loss of body mass, is associated with decreased energy production. Abnormally low levels of L-carnitine (LC) in skeletal muscle means that mitochondrial β-oxidation of long-chain fatty acids (LCFA) does not occur efficiently in patients with CC. We assessed the influence of CC on LC distribution and the effects of parenteral lipid emulsions on plasma LC levels and urinary excretion. Fifty patients with CC were randomly assigned to total parenteral nutrition (TPN) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 22 publications
0
18
0
1
Order By: Relevance
“…In part I of this study (14), a deficiency in LC was found in the skeletal muscles of patients with CC. Muscle degradation is considered to be the main cause, along with dietary restrictions and a decrease in endogenous LC synthesis.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In part I of this study (14), a deficiency in LC was found in the skeletal muscles of patients with CC. Muscle degradation is considered to be the main cause, along with dietary restrictions and a decrease in endogenous LC synthesis.…”
Section: Discussionmentioning
confidence: 64%
“…In Part I of this study (14), we showed that patients with CC have significant shortages of LC in their skeletal muscles. Thus, LC deficiency is likely to be an additional factor that affects hemostasis and the immune system regardless of the type of fat emulsion used.…”
Section: Introductionmentioning
confidence: 69%
“…Long-chain fatty acids (LCFA) require L-carnitine as a transporter into the mitochondrial matrix, while the MCT do not. The L-carnitine concentration in the skeletal muscles and serum is reduced below reference values in CC patients due to the rate of skeletal muscle degradation (secondary to reduced dietary intake of L-carnitine) and loss in urine [ 21 ]. The serum L-carnitine deficiency is replenished from muscle storage after some delay [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In skeletal muscle and heart muscles, carnitine regulates the mitochondrial ratio of free coenzyme A to acyl-coenzyme A, which is required for fatty acid oxidation. People with cancer, especially those underweight or with cachexia, are at risk of and often present with carnitine deficiency (47).…”
Section: Carnitinementioning
confidence: 99%
“…People with cancer often have a decreased caloric intake and increased metabolic requirements, and numerous antineoplastic drugs can interfere with the absorption and synthesis of carnitine (47). This has led to preliminary studies on L-carnitine supplementation in people with cancer cachexia.…”
Section: Carnitinementioning
confidence: 99%